1995
DOI: 10.1111/j.1467-9450.1995.tb00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Facial EMG reactions to facial expressions: A case of facial emotional contagion?

Abstract: Lars-Olov Lundqvist (1995). Facial EMG reactions to facial expressions: A case of facial emotional contagion? Scandinavian Journal of Psychology, 36, 130-141.The purpose of this study is to explore whether subjects exposed to stimuli of facial expressions respond with facial electromyographic (EMG) reactions consistent with the hypothesis that facial expressions are contagious. This study further examines whether males and females differ in facial EMG intensity. Two experiments demonstrated that subjects respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(106 citation statements)
references
References 26 publications
5
98
0
3
Order By: Relevance
“…Previous research supported that women have a higher propensity to congruently respond to emotional stimuli, a phenomenon that was verified in laboratory studies, resorting to facial expressions of emotion (Lundqvist, 2008;SonnbyBorgström, Jönsson, & Svenson, 2008). In our study we found that this tendency also prevailed with vocal stimuli, since the tendency to mimic the other was more prevalent and constant in the women group than in the men group,…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Previous research supported that women have a higher propensity to congruently respond to emotional stimuli, a phenomenon that was verified in laboratory studies, resorting to facial expressions of emotion (Lundqvist, 2008;SonnbyBorgström, Jönsson, & Svenson, 2008). In our study we found that this tendency also prevailed with vocal stimuli, since the tendency to mimic the other was more prevalent and constant in the women group than in the men group,…”
supporting
confidence: 69%
“…Moreover, recent studies resorted to the electromyography technique to test for such differences and found that women respond to emotional stimuli with more pronounced facial electromyography intensity (Lundqvist, 2008) Women's greater sensitivity with regard to recognizing emotions in others is, to a great extent, a perceptual ability based on adaptive mechanisms (Goos & Silverman, 2002). Some authors have related it to the genderrole stereotype of women since, from an early age, they 10 10 Emotional contagion in voice-to-voice are socially expected and motivated to emotionally relate more to others, which might result in a more accurate ability to identify and converge with others' expressions and emotions (e.g., Broverman, Vogel, Broverman, Clarkson, & Rosenkrantz, 1972;Hall, 1978).…”
Section: H4mentioning
confidence: 99%
“…Even though many studies on emotional mimicry also find evidence for a matching subjective experience in the same experiment (e.g., Hess & Blairy, 2001;Lundqvist, 1995), these two do not necessarily co-occur. We use the term emotional DO WE MIMIC WHAT WE SEE OR WHAT WE KNOW?…”
Section: Emotional Mimicry Emotional Contagion and Empathymentioning
confidence: 99%
“…Mood can be elicited when watching positive or negative facial expressions (Lundqvist, 1995) and has been shown to influence information processing. People in a positive mood rely more on heuristics, while people in a negative mood engage in effortful and cautious processing (Bless, Bohner, Schwarz, & Strack, 1990;Bodenhausen, Kramer, & Süsser, 1994).…”
Section: Expressed Emotionmentioning
confidence: 99%